2009
DOI: 10.1007/s11258-009-9684-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of folivory and neighbor plants on Cirsium altissimum (tall thistle) rosette performance

Abstract: Predicting how herbivory and neighbor plant interactions combine to affect host plants is critical to explaining variation in herbivores' impact on plant population dynamics. In a field experiment, we asked whether the combined effects of neighbor plants and folivores upon performance of tall thistle (Cirsium altissimum), a monocarpic perennial, can be predicted as the product of their individual effects (i.e. effects of neighbor plants and folivores act independently in suppressing tall thistle performance). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Shorter height of tall thistles with mined apical meristems may have increased the competitive effect of neighboring grasses. Previously, light competition from grasses at the Ninnescah Reserve has been shown to significantly reduce tall thistle rosette survival (Russell and Spencer, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter height of tall thistles with mined apical meristems may have increased the competitive effect of neighboring grasses. Previously, light competition from grasses at the Ninnescah Reserve has been shown to significantly reduce tall thistle rosette survival (Russell and Spencer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many insects attack C. altissimum . Folivores include the native weevil Baris subsimilis , the exotic weevil Trichosirocalus horridus (Takahashi et al, 2009), larvae of the painted lady butterfly Vanessa cardui , a flea beetle Systena hudsonias (Russell and Spencer, 2010), grasshoppers, and several microlepidopterans (Guretzky and Louda, 1997). Insect herbivores on reproductive tissues include the meristem‐mining moth Platyptilia carduidactyla and two species whose larvae attack developing flower heads: the tephritid fly Paracantha culta and the pyralid moth Homoeosoma eremophasma (Takahashi et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Weinmannia and Fuchsia appear to have comparable competitive abilities to each other irrespective of clipping. This highlights that plant responses to neighbours and competition are not only species‐specific (Reader and Bonser 1998), but also potentially dependent on whether the neighbour is defoliated or not (Hulme 1996, Russell and Spencer 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Weinmannia and Fuchsia appear to have comparable competitive abilities to each other irrespective of clipping. Th is highlights that plant responses to neighbours and competition are not only species-specifi c (Reader and Bonser 1998), but also potentially dependent on whether the neighbour is defoliated or not (Hulme 1996, Russell andSpencer 2010). Coexisting plant species can diff er greatly in their responses to defoliation, and several studies have shown this to be a powerful determinant of plant community composition (Walker andChapin 1987, Buckland andGrime 2000).…”
Section: Discussionmentioning
confidence: 99%